AR-13, a Celecoxib Derivative, Directly Kills Francisella In Vitro and Aids Clearance and Mouse Survival In Vivo - Hoang, Ky V.; Adcox, Haley E.; Fitch, James R.; Gordon, David M.; Curry, Heather M.; Schlesinger, Larry S.; White, Peter; Gunn, John S. (Frontiers in Microbiology, 2017)
Francisella tularensis (F. tularensis) is the causative agent of tularemia and is classified as a Tier 1 select agent. No licensed vaccine is currently available in the U.S. and treatment of tularemia is confined to few antibiotics. In this study, we demonstrate that AR-13, a derivative of the cyclooxygenase-2 inhibitor celecoxib, exhibits direct in vitro bactericidal killing activity against Francisella including a type A strain of F. tularensis (SchuS4) and the live vaccine strain (LVS), as well as towards the intracellular proliferation of LVS in macrophages, without causing appreciable toxicity to these host cells. Identification of an AR-13-resistant isolate indicates that this compound has an intracellular target(s) and that efflux pumps can mediate AR-13 resistance. In the mouse model of tularemia, AR-13 treatment protected 50% of the mice from lethal LVS infection and prolonged survival time from a lethal dose of F. tularensis SchuS4. Combination of AR-13 with a sub-optimal dose of gentamicin protected 60% of F. tularensis SchuS4-infected mice from death. Taken together, these data support the translational potential of AR-13 as a lead compound for the further development of novel, potent anti-Francisella agents.